Shari'a and Politics in Modern Indonesia - Azra, Azyumardi; Salim, Arskal (ISEAS Publishing, 2003)
After the fall of President Soeharto, there have been heightened attempts by certain groups of Muslims to have shari’a (Islamic law) implemented by the state. Even though this burning issue is not new, it has further divided Indonesian Muslims. The introduction of Islamic law would also affect the future of multi-cultural and multi-religious Indonesia. So far, however, the introduction of shari’a nationwide has been opposed by the majority of Indonesian Muslims. This book gives an overview of shari’a from post-Independence in 1945 to the most recent developments in Indonesia at the start of the new millennium